1996
DOI: 10.1159/000129454
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Autologous Fibrin Sealant in Experimental Lung Surgery

Abstract: A controlled study was performed to evaluate the effectiveness and biocompatibility of ethanol-prepared fibrin sealant for closure of an experimental pulmonary air leak in pigs. The sealant was based on co-administration of fibrinogen concentrate prepared from plasma by ethanol precipitation and thrombin solution. Standardized wedge resections were created bilaterally in the lungs of 5 pigs and sutured on both sides. The lungs were randomized for treatment with fibrin glue or as a control no sealant. Chest tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Bearing in mind these variations in study design, it is not surprising that the results differ considerably. 1,[3][4][5][6][7][8][9][10] The conclusion from the literature seems to be that fibrin sealant may reduce a small pulmonary air leakage if it is properly applied with a spray system 11 to a dry lung surface, without bleeding or air leakage, at the time of the application. This means that the lung should not be ventilated for 1 to 2 min while the sealant is allowed to cross-link.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bearing in mind these variations in study design, it is not surprising that the results differ considerably. 1,[3][4][5][6][7][8][9][10] The conclusion from the literature seems to be that fibrin sealant may reduce a small pulmonary air leakage if it is properly applied with a spray system 11 to a dry lung surface, without bleeding or air leakage, at the time of the application. This means that the lung should not be ventilated for 1 to 2 min while the sealant is allowed to cross-link.…”
Section: Discussionmentioning
confidence: 99%
“…A persistent air leak increases the incidence of morbidity and prolongs patient hospitalization, incurring additional expenses. 1 Therefore, expectations are high for the many new types of surgical sealants for pulmonary air leakage that have emerged in the last decade. The aim of this randomized study was to study the effectiveness of a new, autologous fibrin sealant, Vivostat (ConvaTec; Skillman NJ), on air leaks after experimental lung resection in pigs.…”
mentioning
confidence: 99%
“…The system is fully automated and microprocessorcontrolled, and is made up of three components: an automated processor unit, an automated applicator unit, and a disposable, single-patient-use unit, which includes a Preparation set, into which 120 ml of blood is donated, and a Spraypen applicator [2,3]. Although, animal studies have suggested that Vivostat is effective at reducing air leakage following pulmonary resection [4], clinical studies with Vivostat in pulmonary surgery have not been published previously.…”
Section: Introductionmentioning
confidence: 99%
“…Various materials, such as fibrin glue,10–16 cyanoacrylate,17, 18 GRF (gelatin‐resorcinol cross linked with formaldehyde) and GRFG (GRF with glutaraldehyde),19–22 collagen and gelatin‐based tissue adhesives,23–25 and polyurethane‐based adhesives26, 27 have been developed for controlling the leakage of air and body fluid as well as bleeding. In Japan fibrin glue has been widely used since the late 1980s as a sealant material to prevent air leakage from surgical sites on the lung 3, 9.…”
Section: Introductionmentioning
confidence: 99%